FAKTOR-FAKTOR PENENTU KEMENANGAN PETAHANA SEBAGAI CALON PERSEORANGAN DALAM PILKADA DI KABUPATEN REMBANG TAHUN 2015 - Mififtakhul Nurjannah; Muhammad Adnan; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
ABSTRACTLocal election is one of the important instruments in order to realize the life of democracy at local level. Through elections, it is hoped that elected regional heads have legitimacy in the eyes of their citizens because they are directly elected by their constituents. In order to realize democratic elections and uphold equality, not only a policy about party nomination was made, but it was also independen nomination. An independent path is the nomination of a candidate pair without the support of a political party formally with the conditions that have been determined - one of them is the support of ID cards by citizens. In 2015 local elections in Rembang Regency, Abdul Hafidz and Bayu Andriyanto as the pair of number three came out with a 68.50% win. The couple advanced through an independent path. Actually, the independent path is chosen not only because they are non-party people, but also because the party from PPP candidate is experiencing internal conflict at the central level so it cannot be used as a political vehicle in political elections 2015. While Nasdem Party, which is the party of origin of candidate Vice Regent only get vote in Election 2014 equal to6,6%, whereas the requirement to nominate candidates for Regents and Vice Regents are 20%.The victories of Hafidz and Bayu are phenomenal considering they are nominated through independent path. Based on the research conducted by the authors, there are several determinants that affect the victory of Hafidz and Bayu in the 2015 Local election ago. First, the Identification of PPP and Nasdem party voters. Evenhough Hafidz nominate himself as an independent candidate, but the party machine is engaged in mobilizing voters' votes to influence the voter networks of both parties. The second factor is candidate. The figure of Hafidz as an incumbent influenced his victory in elections in 2015. Added to the background of Hafidz as a religious figure who often fill the recitation also provides social capital from the congregation. The last factor is the success of the work program. One of the work programs known during Hafidz's previous tenure was to raise the salary of a ‘madrasah’ teacher. The success of a good work program can foster public confidence so that Hafidz is re-elected in the 2015 elections.Keywords: Candidate, Independent, Local Election, Party Machine.1. Pendahuluan